Dynamic Changes in Equatorial Segment Protein 1 (SPESP1) Glycosylation During Mouse Spermiogenesis - Suryavathi, Viswanadhapalli (Biol Reprod, 2015)
ESP1/SPESP1 is a testis-specific, postmeiotic gene expressed in round spermatids that encodes equatorial segment protein 1, an intra-acrosomal protein found in the acrosomal matrix and on the luminal surface of the inner and outer acrosomal membranes within the equatorial segment domain of mature spermatozoa. A comparison of testicular protein extracts with caput, corpus, and caudal epididymal sperm proteins revealed striking differences in the apparent masses of SPESP1 isoforms. The predominant isoforms of SPESP1 in the testis were 77 and 67 kDa, with 47-kDa forms present to a minor degree. In contrast, SPESP1 isoforms of 47 and 43 kDa were found in caput, corpus, and caudal sperm, indicating that SPESP1 undergoes noticeable mass changes during spermiogenesis and/or subsequent transport to the epididymis. On two-dimensional (2D) SDS-PAGE, testicular SPESP1 isoforms resolved as a train of pI values from 4.9 to 5.2. Immunoprecipitated 77-kDa SPESP1 from testis reacted with the glycoprofile stain after one-dimensional and 2D gel electrophoresis, indicating that the 77-kDa testicular isoform was highly glycosylated. One charge variant of the 67-kDa isoform was also glycoprofile positive after 2D gel resolution. The 47- and 43-kDa isoforms of SPESP1 from epididymal sperm did not stain with glycoprofile, suggesting an absence of, or few, glycoprofile-sensitive glycoconjugates in epididymal SPESP1. Treatment of testicular extracts with a variety of glycosidases resulted in mass shifts in immunoreactive SPESP1, indicating that testicular SPESP1 was glycosylated and that terminal sialic acid, N- and O-glycans were present. A mixture of deglycosidase enzymes (including PNGase-F, neuraminidase, beta1–4 galactosidase, endo-alpha-N-acetylgalactosaminidase, and beta N-acetyl-glucosaminidase) completely eliminated the 77- and 67-kDa SPESP1 bands and resulted in the appearance of 75-, 60-, 55-, 50-, 47-, and 43-kDa forms, confirming that both the 77- and 67-kDa testicular forms of SPESP1 contain complex carbohydrate residues. Treatment of caudal epididymal sperm with PNGase-F enzymes showed a faint deglycosylated band at 30 kDa, but neuraminidase did not result in any molecular shift, indicating that epididymal sperm SPESP1 did not contain sialic acid/N-acetylglucosamine residues. These findings are consistent with the hypothesis that SPSPESP1 undergoes significant glycosylation in the testis and that the majority of these glycoconjugates are removed by the time sperm reach the caput epididymis. Studies of the fate of SPESP1 after the acrosome reaction localized SPESP1 to the equatorial segment region in both noncapacitated and capacitated, acrosome-reacted sperm. During capacitation, SPESP1 underwent proteolysis, resulting in a 27-kDa fragment. Zona-free oocytes incubated with recSPESP1 protein showed complementary binding sites on the microvillar oolemmal domain. Both recSPESP1 and anti-recSPESP1 antibody inhibited in vitro fertilization.